The Locus of Control Moderates The Relationship between Leadership Style, Quality of Human Resources, and Commitment to Managerial Performance Budgeting (Study of The Regional Goverments in Sidoarjo Regency): [Locus of Control Memoderasi Hubungan Gaya Kepemimpinan, Kualitas Sumber Daya Manusia, serta Komitmen terhadap Kinerja Manajerial Penyusunan Anggaran (Studi Pada Pemerintah Daerah Kabupaten Sidoarjo)] - Cut Ami Rahmah; Sarwenda Biduri; Sigit Hermawan; Hadiah Fitriyah (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Sidoarjo Regency, as the second largest APBD recipient in East Java, still has SiLPA realization was effective less and efficient less due to the budget not being fully absorbed. The purpose of this study was to determine the effect of leadership style, HR quality, and commitment with locus of control moderation on managerial performance in budgeting. This study used a quantitative approach which was analyzed using the SmartPLS statistical program (v.3.2.9). The data collection technique was in the form of a closed questionnaire via Google Forms to the research subjects of structural officials of the Sidoarjo Regency regional apparatus using a Likert scale with a purposive sampling method. The population of this study were 48 Regional Officials in Sidoarjo Regency, with a total of 192, total sample was 64 respondents. Data quality test is carried out through validity testing, reliability testing, hypothesis testing through bootstrapping. The results showed that leadership style and commitment had a effect on managerial performance in budgeting, while the quality of human resources had a uneffect on managerial performance in budgeting. Then locus of control can moderate and strengthen the relationship between HR quality and commitment to managerial performance in budgeting, while locus of control is unable to moderate or strengthen the relationship between leadership style and managerial performance in budgeting. The results of this study are expected to be able to increase the efficiency and effectiveness of budgeting in the Regional Government of Sidoarjo Regency.